The Relationship Between Mental State and Functional Status in Elderly Residents of Kahrizak - Hadi Kazemi; Sima Ghasemi; Farshad Sharifi; Hossein Fakhrzadeh; Maryam Ghaderpanahi; Mojde Mirarefin; Mahshid Foroughan; parvaneh Mohammadkhani (University of Social Welfare & Rehabilitation Sciences, 2010)
Objectives: The current study was performed to investigate the relationship between mental impairment and each component of activity of daily living (ADL) in elderly residents of the Kahrizak Charity Foundation. Methods & Materials: Standardized Iranian Mini Mental examination and Barthel index were used to assest cognitive status and ADL in 184 elderly residents of Kahrizak, respectively. Results: Data showed that 31.7% of participants had normal cognitive status and 63.3% had cognitive impairment. There was significant relationship between cognitive status and ADL after adjustment for confounding factors (P=0.01, r=0.2). By using multiple logistic regression analysis, the relation between cognitive impairment and functional status was examined (P=0.05). Odd ratio of functional disability showed an increasing trend with increasing severity of cognitive impairment [Odd Ratio (OR) mild cognitive impairment: 1.13, Confidence Interval (CI): 0.54-2.37 OR moderate to severe cognitive impairment: 3.67, CI: 0.39-34.35]. Regarding the relation between Barthel components and cognitive status it was showed that there was a significant association between independent bathing and cognitive status (OR: 2.33, CI: 1.14-4.72) as well as movementability with cognitive impairment (OR: 2.96, CI: 1.30-6.75). Conclusion: Cognitive status can be a predictive factor of ADL inelderly subjects.